The Hungarian Community in Mamluk Egypt - Desouki Mohamed Hassan, Mohamed (Études sur la Région Méditerranéenne, 2021)
The Hungarian community had no noticeable activity in the era of Mamluk period 1250– 1382, and that’s because of their small numbers which no one can observe their roles in that period. In addition to that, the Islamic sources do not name any strange population by its names or nationality but reported them as the Franks. Even foreign sources and travelers books in the same period did not mention the names or groups that had a prominent role in the Egyptian society in the Mamluk era in that period. So the researcher cannot link the term Franks and any groups or individuals who had a significant role in the Egyptian society during the period under study. By the end of the first half of the 14th Century, the Eighth Century AH, the Ottoman Empire appeared as a new force in the area to increase the conflict between the East and the West. The ambitions of the Ottoman Empire exceeded the maritime boundary between it and Europe, so the military clash resulted a large number of Hungarian prisoners, and with many wars and victories the palaces of the Sultans had been filled by them. The Ottoman Sultans sent large numbers of Hungarian prisoners as gifts to the Mamluk Sultan in Cairo, as an expression to their victory, and the great role they played to support the Islam. As a result of the large number of those prisoners, the Ottoman Empire slave markets were filled with them, so they had been sent to other markets, and Egypt was the first destination for releasing this quantity of prisoners. Genoa played a great role in transferring these prisoners for sale in slave markets in Egypt. By the time, in the 15th Century AD, the Ninth AH, the Hungarian community ranked first level among all Mamluks coming from the European lands. They entered into the sultan’s entourage, or came to the service of princes, and some of them joined the military teams. The writings of foreign travelers who visited Egypt during this century confirmed that Hungarians represented the largest number of the other Mamluks who came from European continent. Despite Hungarians involvement in the Egyptian society in the Mamluk era, and despite their respect for the saying “peoples on the religion of their kings”, they have often expressed their culture of traditions and customs. Some of them convinced by Islam, some of whom embraced it to escape tribute or imprisonment. That latter category in the late Mamluk period, brought actions contrary to Islamic law and Egyptian society traditions, the matter forming diseases that contributed significantly to the collapse of country power. The researcher relied on many Arab sources, writing of foreign travelers and some Turkish sources; trying to compare and link between what came in these sources, to reach the nature of the life of that community within the Egyptian society in the Mamluk era.